2021
DOI: 10.3354/esr01137
|View full text |Cite|
|
Sign up to set email alerts
|

Residency, demographics, and movement patterns of North Atlantic right whales Eubalaena glacialis in an offshore wind energy development area in southern New England, USA

Abstract: Offshore wind energy development is growing quickly around the world. In southern New England, USA, one of the largest commercial offshore wind energy farms in the USA will be established in the waters off Massachusetts and Rhode Island, an area used by the Critically Endangered North Atlantic right whale Eubalaena glacialis. Prior to 2011, little was known about the use of this area by right whales. We examined aerial survey data collected between 2011-2015 and 2017-2019 to quantify right whale distribution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 84 publications
2
12
0
Order By: Relevance
“…Our results and those of Quintana-Rizzo et al 49 demonstrate a novel summer occurrence of right whales in SNE from 2017 to 2019. The energetic tradeoffs of a long migration to other feeding grounds, such as the Gulf of St Lawrence, may increase the appeal of SNE to right whales during the summer months.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results and those of Quintana-Rizzo et al 49 demonstrate a novel summer occurrence of right whales in SNE from 2017 to 2019. The energetic tradeoffs of a long migration to other feeding grounds, such as the Gulf of St Lawrence, may increase the appeal of SNE to right whales during the summer months.…”
Section: Discussionsupporting
confidence: 85%
“…The recent, year-round detection of right whales in SNE by aerial surveys is unique among major right whale habitats. Our analyses and previous studies 49 , 58 suggest that SNE represents an increasingly important habitat for the declining right whale population.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that the abundance of female right whales increased over the 41 year study period from 81 in 1985, peaking at 185 individuals (95% CI: 183-187) in 2010 (Figure 2A), after which their abundance plateaued to 2013, then declined from 184 individuals in 2013 to 142 individuals at the beginning of 2018 (95% CI: 135-150). This coincides with a post-2010 change in the general distribution of NARW (Davis et al, 2017), and with an influx of NARW into the Gulf of St Lawrence post-2014 (Simard et al, 2019), and increased use of a foraging area in offshore, southern New England in recent years, particularly 2017(Quintana-Rizzo et al, 2021. Both of these sites, when NARW started using them, lacked spatially-explicit management programs to minimize NARW morbidity and mortality.…”
Section: Discussionmentioning
confidence: 75%
“…Given that less than half of the NARW population has been sighted in the GSL beginning in May through December, locating the remaining portion of the population during the summer season (June-August) is critical (Crowe et al, 2021). While this present study did not show evidence of unidentified high-use habitats in Canadian waters, summertime (August) NARW aggregations have been observed south of the Gulf of Maine in the Nantucket Shoals region, suggesting the population could be spread out both north and south of the Gulf of Maine (RWSAS, n.d. Northeast Fisheries Science Center, 2020;Quintana-Rizzo et al, 2021). Continued persistent and improved monitoring is crucial to locate as yet unidentified habitats where whales may be aggregating .…”
Section: Seasonal Distribution In Northern Canadian Watersmentioning
confidence: 99%